2020
DOI: 10.1371/journal.ppat.1008886
|View full text |Cite
|
Sign up to set email alerts
|

The immunity of Meiwa kumquat against Xanthomonas citri is associated with a known susceptibility gene induced by a transcription activator-like effector

Abstract: Citrus canker caused by Xanthomonas citri subsp. citri (Xcc) is one of the most devastating diseases in citrus. Meiwa kumquat (Fortunella crassifolia) has shown a durable resistance against Xcc. Here, we aimed to characterize the mechanisms responsible for such a durable resistance by characterizing the transcriptional and physiological responses of Meiwa kumquat to Xcc. Inoculation of Meiwa kumquat with Xcc promoted immune responses such as upregulation of PR genes, accumulation of salicylic acid, hypersensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 86 publications
5
20
0
Order By: Relevance
“…It has been reported that cultivated citrus varieties are more susceptible to canker disease than wild citrus, and that wild citrus varieties have a broad spectrum of disease resistance, whereas cultivated citrus varieties have lost certain resistance to different degrees during domestication [2,6]. For example, Meiwa kumquat obtain a durable resistance to Xcc by upregulating a host susceptibility gene to elicit immune responses [31]. Tracing back to wild germplams is an alternative strategy for identifying gene resources for breeding purpose.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that cultivated citrus varieties are more susceptible to canker disease than wild citrus, and that wild citrus varieties have a broad spectrum of disease resistance, whereas cultivated citrus varieties have lost certain resistance to different degrees during domestication [2,6]. For example, Meiwa kumquat obtain a durable resistance to Xcc by upregulating a host susceptibility gene to elicit immune responses [31]. Tracing back to wild germplams is an alternative strategy for identifying gene resources for breeding purpose.…”
Section: Discussionmentioning
confidence: 99%
“…Designer TALEs (dTALEs) containing the repeat arrays elaborated in Fig 3A were constructed using “Golden Gate TALEN and TAL Effector Kit 2.0” as previously described [ 77 ] and cloned into pTAL2 as a final destination vector. The pTAL2 PstI/EcoRI fragments containing the dTALEs were cloned into pBBRNPth [ 54 ] and transformed into Xcc pthA4 :Tn5 [ 61 ] by electroporation. Expression of all constructed dTALEs and their adapted derivatives in Xcc was validated by Western blot [ 78 ] using Anti-HA High Affinity antibody (Roche diagnostics, Basel, Switzerland) ( S4 Fig ).…”
Section: Methodsmentioning
confidence: 99%
“…Ralstonia solanacearum strains that experimentally evolved on bean plants harbored a mutation in the transcriptional regulator efpR , which regulates EPS production, motility and numerous metabolic processes [ 51 , 52 ]. Xcc strains that evolved in resistant Meiwa kumquat via repeated inoculation and isolation harbored point mutations in the pthA4 TALE that was later verified to be associated with elicitation of immune responses [ 53 , 54 ].…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, Xanthomonas citri subsp. citri, another bacterial pathogen of citrus, infection of kumquat ( Citrus japonica , syn: Fortunella crassifolia ) triggers H2O2 production at 2 days after inoculation which peaks (9.86 µmol g −1 FW) at 8 days after inoculation, eventually leading to cell death 23, 24 . X. citri subsp.…”
Section: Hlb Caused Cell Death Is Instigated By Rosmentioning
confidence: 99%
“…X. citri subsp. citri induced cell death is a slow process and happens at approximately 6-8 days after inoculation 24 . Hence, we conjectured that ROS induced by CLas reaches the threshold necessary to trigger the death of companion and sieve element cells in mature leaves, but possibly not in the early stage of infection of young leaves before CLas titers reach a certain threshold.…”
Section: Hlb Caused Cell Death Is Instigated By Rosmentioning
confidence: 99%